Incidence of acute otitis media from 2003 to 2019 in children ≤ 17 years in England - Salini Mohanty; Bélène Podmore; Ana Cuñado Moral; Thomas Weiss; Ian Matthews; Eric Sarpong; Ignacio Méndez; Nawab Qizilbash (BMC, 2023)
Abstract Background The 7-valent pneumococcal conjugate vaccine (PCV7) was introduced in 2006 and the 13-valent pneumococcal conjugate vaccine (PCV13) in 2010 in the UK. PCVs are active immunization for the prevention of invasive disease, pneumonia and acute otitis media (AOM) caused by Streptococcus pneumoniae in children. The aim of this observational study was to estimate incidence rates (IRs) of AOM in children ≤17 years from 2003 to 2019 in England, before and after the introduction of pneumococcal conjugate vaccines (PCVs). Methods AOM episodes were identified using Read diagnosis codes in children aged ≤17 years in the Clinical Practice Research Datalink (CPRD) Gold database from 2003 to 2019. Annual IRs with 95% confidence intervals (CI) by age group were calculated as the number of episodes/person-years (PY) at risk. Interrupted time series analyses were conducted to estimate incidence rate ratios (IRR) across post-PCV7 (2007-2009), early post-PCV13 (2011-2014) and late post-PCV13 (2015-2019) periods compared to the pre-PCV7 period (2003-2005) using generalized linear models. Results From 2003 to 2019, 274,008 all-cause AOM episodes were identified in 1,500,686 children. The overall AOM IR was 3690.9 (95% CI 3677.1-3704.8) per 100,000 PY. AOM IRs were highest in children aged < 5 years and decreased by age; < 2 years: 8286.7 (95% CI 8216.8-8357.1); 2-4 years: 7951.8 (95% CI 7902.5-8001.4); 5-17 years: 2184.4 (95% CI 2172.1-2196.8) (per 100,000 PY). Overall AOM IRs declined by 40.3% between the pre-PCV7 period and the late-PCV13 period from 4451.9 (95% CI 4418.1-4485.9) to 2658.5 (95% CI 2628.6-2688.7) per 100,000 PY, and across all age groups. IRRs indicated a significant decrease in AOM IRs in all the post-vaccination periods, compared to the pre-PCV7 period: post-PCV7 0.87 (95% CI 0.85-0.89), early post-PCV13 0.88 (95% CI 0.86-0.91), and late post-PCV13 0.75 (95% CI 0.73-0.78). Conclusions The AOM IRs declined during the 2003-2019 period; however, the clinical burden of AOM remains substantial among children ≤17 years in England.